The Effect Of Work-Family Conflict And Work Stress On Employee Performance During The Covid-19 Pandemi (Study on Employees of PT. Kreasi Kotak Megah) - Laya Azani Lubis; Onan Marakali Siregar (Journal of Economics and Business (JECOMBI), 2023)
Performance is the result of work that can be achieved by an employee in a company in accordance with the goals and standards set by the company. Optimizing performance, employees must be supported by excellent physical and psychological conditions. One that affects the psychological condition of employees is work-family conflict and work stress. Work-family conflict is a conflict between work and family roles that arise from home, while work stress arises from the company. If work-family conflict and work stress are high, it will cause employees not to focus on doing their jobs which will have an impact on employee performance. This study aims to analyze the effect of work- family conflict and work stress on the performance of employees of PT. The creation of the Tanjung Morawa Magnificent Box during the covid-19 pandemic. This study uses quantitative methods involving 67 respondents as research samples. Sampling was done through simple random sampling technique. Collecting data using a questionnaire distributed to respondents. The data analysis method used is validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that the variables of work-family conflict and work stress together have a significant effect on employee performance. The influence given by the work-family conflict and work stress variables contributed 29.2% to the employee performance variable.